1994
DOI: 10.1200/jco.1994.12.12.2682
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of outpatient weekly paclitaxel and concurrent radiation therapy for advanced non-small-cell lung cancer.

Abstract: Esophagitis is the principle dose-limiting toxicity of weekly paclitaxel and thoracic radiation in the outpatient setting. A phase II trial using concurrent radiation and paclitaxel at the MTD of 60 mg/m2/wk is underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(46 citation statements)
references
References 0 publications
1
42
0
3
Order By: Relevance
“…The overall responses (PR) were 78.3% (9/11). These are similar to the results reported by Choy et al [15,16] and Zhu et al [14] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The overall responses (PR) were 78.3% (9/11). These are similar to the results reported by Choy et al [15,16] and Zhu et al [14] .…”
Section: Discussionsupporting
confidence: 83%
“…Concurrent treatment has the advantage of the simultaneous delivery of two cytotoxic treatment modalities, a reduction in overall treatment time, and most importantly, radiosensitization by the chemotherapeutic agents [11,12,16] . NSCLC patients treated with CCRT with nearly full dose of chemotherapy were usually at high risk of severe toxicity of radiation pneumonitis, oesophagitis and neutropenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemotherapeutic agent paclitaxel is used frequently to treat ovarian, breast, and lung cancer (Rowinsky et al, 1990;Rowinsky et al, 1993;Choy et al, 1994;Gianni et al, 1995). Mechanisms of paclitaxel-induced neuropathy remain unknown, although there is growing evidence that paclitaxel administration targets peripheral sensory neurons, leading to damage of neuronal mitochondria (Varbiro et al, 2001;Flatters and Bennett, 2006;Peters et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…These agents have been compared with each other in a phase III study performed in patients with advanced NSCLC, and several studies have suggested the radiosensitising properties of these new agents (Tishler et al, 1992;Leonard et al, 1996;McGinn et al, 1996;Okishio et al, 1996). However, the phase I and II studies combining these agents with radiotherapy have mostly been preliminary (Choy et al, 1994;Greco et al, 1996;Gregor, 1997;Mauers et al, 1998;Herscher et al, 1998). Irinotecan has a mechanism of action targeting the nuclear enzyme topoisomerase I as radiosensitiser in vitro (Okishio et al, 1996).…”
mentioning
confidence: 99%